Westworld [videorecording (DVD)] - Crichton, Michael, 1942-2008; Crichton, Michael, 1942-2008; Brynner, Yul; Benjamin, Richard, 1938-; Brolin, James, 1940-; Oppenheimer, Alan; Van Patten, Dick (Turner Entertainment : Distributed by Warner Home Video, 2010)
This story of a technological paradise suddenly turned nightmare is a genuine shocker. For $1,000 a day, vacationers can indulge whims at the "theme park" called Westworld where the gunhands and dance-hall girls are all robots programmed to serve the guests' violent and lustful fantasies--until something goes wrong with their circuitry.